A Real-Business-Cycle model with search-and-matching frictions and efficiency ("fair") wages - Aleksandar Vasilev (Journal of Economics and Econometrics, 2021)
In this paper we combine two important ingredients - search and matching frictions and "fair wages," and investigate their combined quantitative importance in explaining fluctuations in Bulgarian labor markets. Overall, the calibrated real-business-cycle model for Bulgaria after the introduction of the currency board, when featuring both search- and-matching frictions, and reciprocity in labor relations, performs better vis-a-vis data, and in addition dominates the model with search frictions only (Vasilev 2016a), and setups with efficiency wages alone (Vasilev 2017a,b). The search and matching mechanism captures the volatility of unemployment, while the efficiency wage mechanism fits better the cyclicality of the wage rate.
Keywords: E32; E24; J41; 330; general equilibrium; reciprocity; gift exchange; efficiency wages; unemployment